PENGARUH KEMAMPUAN METAKOGNITIF TERHADAP KEMAMPUAN PEMECAHAN MASALAH PADA MAHASISWA PROGRAM AKADEMIK DAN PROFESI FAKULTAS KEDOKTERAN - Poncorini Pamungkasari, Eti; Murti, Bhisma; Mudjiman, Haris (Jurnal Kedokteran YARSI, 2007)
Problem solving ability is one of several competences that should be mastered by medical graduates. Metacognitive skill, which refers to skills of thinking about thinking, is presumed in the literature to have some relation with problem solving ability. This study aims to investigate the effect ofmetacognitive skill on problem solving ability among medical students of academic and professional programmes at the Faculty of Medicine. This study is analytic and observational, conducted at the Faculty of Medicine, Sebelas Maret University. The study subjects are medical students currentlyundertaking academic or professional programme at the Faculty of Medicine, Sebelas Maret University. Subject were selected purposively by distinguishing sub populations undertaking academic and professional programmes. From each sub population, 20 subjects were selected atrandom to result in a total of 40 subjects for this study. The data were collected by use of a questionnaire that has been previously designed by researchers abroad. The questionnaire was translated from English to Indonesian, modified accordingly, and subsequently tested for its validityand reliability, before use. The data were analyzed employing multiple linear regression model. The results of the regression analysis show that one score in metacognitive skill increases 0.71 score in problem solving ability (?= 0.71; 95%CI 0.37 to 1.06). In addition, students at the professional programme on average have problem solving ability 11.36 scores higher than those at the academic programme (?= 11.36; 95%CI 2.00 to 20.71). This study concludes that there is a statisticallysignfificant effect of metacognitive skill on problem solving ability among medical students at the Faculty of Medicine. After controlling for confounding factors such as learning stages, age, and sex, an increase in metacognitive skill will signficantly increase problem solving ability.